2021
DOI: 10.1080/11101849.2021.1953832
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided suprazygomatic maxillary nerve block in cleft palate surgery: The efficacy of adding dexmedetomidine to bupivacaine

Abstract: We have hypothesized that adding dexmedetomidine to bupivacaine in bilateral ultrasoundguided suprazygomatic maxillary nerve block (SMB) would provide prolonged postoperative analgesia following cleft palate (CP) repair. Children posted for CP repair were randomized to receive bilateral ultrasound-guided SMB, with either 0.15 ml/kg 0.25% bupivacaine on each side (B group; n = 40) or 0.5 µg/kg dexmedetomidine plus 0.15 ml/kg 0.25% bupivacaine on each side (BD group; n = 40). Children and Infants Postoperative P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Comparatively, our results showed a significant reduction in NRS scores at 36 hours post-surgery, which coincided with the time of removal of the haemostatic agent (described as the most unbearable pain ever by most of the patients), as we used 1 ml dexamethasone as an adjuvant with an additional 1.5 mL of 0.5 % bupivacaine in the MNB. Similarly, Mansour RF and Abdelghany (15) showed that administering 0.5 µg/kg dexmedetomidine as an adjunct to bupivacaine 0.25 % in MNB to children assigned for the surgical correction of cleft palates resulted in prolonged postoperative analgesia and decreased total analgesic consumption.…”
Section: Discussionmentioning
confidence: 95%
“…Comparatively, our results showed a significant reduction in NRS scores at 36 hours post-surgery, which coincided with the time of removal of the haemostatic agent (described as the most unbearable pain ever by most of the patients), as we used 1 ml dexamethasone as an adjuvant with an additional 1.5 mL of 0.5 % bupivacaine in the MNB. Similarly, Mansour RF and Abdelghany (15) showed that administering 0.5 µg/kg dexmedetomidine as an adjunct to bupivacaine 0.25 % in MNB to children assigned for the surgical correction of cleft palates resulted in prolonged postoperative analgesia and decreased total analgesic consumption.…”
Section: Discussionmentioning
confidence: 95%
“…For this reason, we did not expect a difference in anesthetic requirements intraoperatively given that the incision was made immediately before block onset. Drawing from insights in the literature on cleft palates and SZMN blocks, 40,[67][68][69][70] it becomes evident that the block's effects on pain typically dissipate within the initial postoperative day. Although it is known that pediatric posttonsillectomy pain can be substantial for up to 7 days postoperatively, our study could not draw any conclusions from pain scores after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dexmedetomidine as an adjuvant to bupivacaine for suprazygomatic maxillary nerve blocks was compared with blocks with bupivacaine alone in three RCTs. [22][23][24] Mansour and Abdelghany 22 investigated the effect of 0.5 mcg/kg dexmedetomidine as an adjuvant to bupivacaine 0.25% for maxillary nerve blocks. While postoperative pain was comparable to the control group during the first 6 postoperative hours, a clinically significant reduction in pain scores was found between 8 and 24 hours postoperatively in the dexmedetomidine group compared with bupivacaine alone.…”
Section: Dexmedetomidine As Adjuvant For Peripheral Nerve Blocksmentioning
confidence: 99%
“…In the three studies mentioned above, [22][23][24] basic analgesia was only mentioned by Mansour and Abdelghany. 22 The use of ultrasound guidance was described in two of the studies.…”
Section: Dexmedetomidine As Adjuvant For Peripheral Nerve Blocksmentioning
confidence: 99%